Modeling And Static Analysis of Vertical Pressure Vessel on PT. X Under Hoop and Longitudinal Stress Condition - Liza, M Prama Diva; Putra, Risky Utama; Basri, Hasan (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2025)
The inspection and testing of the vertical pressure vessel at PT. X were conducted to assess its structural integrity and ensure operational safety. The study focused on thickness and hardness measurements, along with computational stress analysis using the Finite Element Method (FEM). The results revealed an average material thickness of 4.98 mm and an average hardness of 130 HV, indicating compliance with basic material specifications. Stress distribution analysis showed maximum hoop stress of 221.429 MPa and longitudinal stress of 88.111 MPa, both within the material's allowable stress limit of 285.18 MPa. Static displacement analysis identified a maximum displacement of 6.553 mm and a minimum of 0.018 mm, with clear visualization of deformation patterns. These findings confirm the vessel's design safety and its ability to withstand operational pressures without failure.